Perspectives and Implementation of Multicultural Education: A Comparative Study between Developed and Developing Countries - Mukhlis Mukhlis; Muhammad Hasan Basari; Fitri Handayani (Integrated Education Journal, 2024)
Multicultural education has become a crucial approach in responding to the growing global social diversity. This study aims to compare the perspectives and implementation of multicultural education in developed and developing countries. Using a qualitative approach, this research analyzes the multicultural education policies, challenges faced, and implementation strategies in both types of countries. The findings reveal that developed countries, with better educational resources and infrastructure, tend to have more structured and inclusive approaches to multicultural education, although they still face issues such as social segregation and inequality of access. In contrast, developing countries, despite facing significant challenges related to limited resources and socio-economic disparities, demonstrate more adaptive approaches in integrating multicultural values into their curricula. This study highlights the importance of local context in developing effective educational policies and practices to foster more inclusive and tolerant societies. The findings can serve as a reference for policymakers and educators in designing multicultural education programs that are more responsive to the needs of their respective communities